Development of Adult Worms and Granulomatous Pathology Are Collectively Regulated by T- and B-Cells in Mice Infected with Schistosoma japonicum - Tang, Hongbin (Public Library of Science, 2013)

(untitled)
Schistosoma blood flukes, which cause schistosomiasis affecting 200 million people in the world, are dependent on signals from host CD4(+) T cells to facilitate parasite growth and development in the mammalian host and to induce Th2-biased inflammatory granulomas. B cells, however, are reported to down-regulate granulomatous pathology in schistosomiasis, but not to affect the development of blood flukes together with CD4(+) T lymphocytes. Thus it is not clear whether B cells mediate parasite development, reproduction and egg granuloma formation of schistosomes without the help of CD4(+) T lymphocytes. Using mice that have severe combined immunodeficiency (scid) and mice lacking T cells (nude), we found that the absence of B cells can more seriously hamper the development and paring of adult worms, but granuloma formation of Schistosoma japonicum in scid mice was not down-regulated comparing with that in nude mice. The level of IL-10 in the sera of nude mice was significantly higher than of scid mice at 43 days post infection (p.i.). Thus multiple mechanisms of immune modulation seem to be involved in parasite development and reproduction by helminth-induced regulatory B cells. Our findings have significance for understanding the molecular connections between schistosomes and T- and B-cells, indicating that more research is needed to develop efficient vaccine-based therapies for schistosomiasis.